Improvement of rust resistance and FHB resistance QTL in wheat through the application of an integrated biotechnology approach - Meintjes, Schalk Willem (Stellenbosch : Stellenbosch University, 2017)
Thesis (MSc)--Stellenbosch University, 2017.